Interrogation Sensing Scheme Based on a Figure-of-Eight Fiber Loop Mirror - Silva, Ricardo M. (2019)
A fiber optic interrogation sensor scheme based on a “figure-of-eight” configuration created from a single directional 3 × 3 fiber optic coupler is proposed. Two loops are formed in each arm and one of them contains the sensing head and the other is used as reference signal. A theoretical study based on Jones matrix analysis of this fiber loop mirror combination is reported. The optical configuration is tested as an interrogation scheme for a fiber strain sensor where the spectral response arises from the combination of the reference signal modulated by the sensor signal. The strain sensor configuration shows a phase sensitivity of 6.7 ± 4.38 × 10−2 mrad/μstrain by linear regression.